DIDACTIC CONDITIONS FOR INCREASING EFFICIENCY DIALOGUE LEARNING IN FORMATION COGNITIVE ACTIVITY OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the sum of the conditions which influence forming of cognitive activity in the process o f dialogue education.